Mineralogy, geochemistry and monazite U-Th-Pb geochronology of the Hakimpur banded iron formation deposit, Bangladesh: a petrogenetic study - Hasan, A S M Mehedi; Hossain, Ismail; Tsunogae, Toshiaki; Sahiduzzaman, Md; Yeasmin, Zareen; Alam, Md Sha; Akbar, Md Ali; Zaman, Mohammad Nazim (Bangladesh Journal of Scientific and Industrial Research, 2023)
The Fe-rich deposits from Hakimpur (Bangladesh) are associated with a broad range of rock types including BIF, biotite schist, quartzite and amphibolite. Geochemical analysis coupled with petrographic studies indicates the BIF and BIF-hosted rocks were derived from sedimentary protoliths. In the sediments, clay minerals were altered at a certain thermobarometric condition during metamorphism: Clay (illite) → chlorite → biotite → amphibole, which is evident from silicification, chloritization, biotitization, saussuritization and epidotization in petrographic results. Monazite chemistry U-Th-Pb geochronological evidence indicates the deposit was affected by a single, medium-grade metamorphic event that occurred at 1728±28 Ma during the Basement rock’s magmatic event activated. The metamorphic alteration was took place by the hydrothermal action or orogenic activity due to magmatism of Palaeoproterozoic basement rock occurred surrounding the areas. The temperatures condition and oxygen fugacities obtained from zircon and coexisting magnetite and ilmenite assemblages [677–692°C and 522–809°C (at 10-23.9 to 10-11.9 fo2), respectively] are partly compatible with known crystallization conditions of the dioritic basement rock in Bangladesh. Bangladesh J. Sci. Ind. Res. 58(4), 241-264, 2023